Identifying optimal early‐season harvest timing in annual fall forages. Issue 2 (7th July 2022) - Billman, Eric D.; de Souza, Igor Alexandre; Smith, Richard G.; Soder, Kathy J.; Warren, Nicholas D.; Brito, André F.
Abstract: Fall forage production in the northeastern United States is complicated by early onset of cool temperatures, limiting forage availability in cool‐season perennials. Annual forages planted in late summer as cover crops or supplemental forage crops may fill this niche; however, data on their nutritive value over the short fall harvest window is lacking. This study compared six annual forage crops for their forage mass and nutritive value and identified optimal harvest times based on changes between forage mass and digestibility. Monocultures of canola ( Brassica napus L.), forage radish ( Raphanus sativus L.), oat ( Avena sativa L.), spring triticale (× Triticosecale Wittm. ex A. Camus [ Secale × Triticum ]), spring wheat ( Triticum aestivum L.), sunn hemp ( Crotolaria juncea L.), and a mixture of all six species were sown in August of 2015 and 2016 then harvested at three time points (6, 8, and 10 weeks after planting [WAP]) over the fall (September–November). Canola, oat, and spring wheat had the greatest forage mass, while sunn hemp had the least across all harvests. Canola and forage radish had the lowest neutral detergent fiber (NDF) and acid detergent fiber (ADF) and greatest in vitro true dry matter digestibilities (IVTDMd) across all harvests, while sunn hemp and the grasses declined in IVTDMd after first and second harvest. Forage mass of the fall mix was comparable to the highest yielding monoculture at third harvest only. Results suggest that forage brassicas can be harvested without compromising mass or nutritive value, while cereal grasses gained forage mass at the expense of nutritive value. Core Ideas: Annuals sown in late summer for fall forage have a short window for growth. Brassicas maintain high forage mass and nutritive value throughout fall. Cereal grasses produce the most forage mass, but digestibility declines after mid‐fall. The warm‐season legume sunn hemp had poor forage mass and nutritive value at all harvests.